The determination of oxidation rates and quantum yields during the photocatalytic oxidation of As(III) over TiO2 - Heiba,HF; Bullen,JC; Kafizas,A; Petit,C; Skinner,SJ; Weiss,D (Journal of Photochemistry and Photobiology A: Chemistry, 2022)
The determination of reaction rates for the photocatalytic oxidation (PCO) of arsenite (As(III)) using TiO2 under UV radiation is challenging due to the numerous experimental processes. This includes chemical processes running simultaneously with PCO (e.g. adsorption of arsenic species, direct UV photolysis of As(III)) and the analytical approach used (e.g. whether As(III) or As(V) are measured and used in the calculation of the PCO rate). The various experimental approaches used to date have led to oxidation rates and rate constants which vary by orders of magnitude and contradicting information on rate laws. Here we present the results of a critical examination of possible controls affecting the experimental determination of PCO rates. First, we demonstrate that the choice of analytical technique is not critical, provided that the rate constants are calculated based on the depletion of As(III) after correction of the directly adsorbed As(III). Second, we show the correction of the directly adsorbed As(III) at each time interval is best done by running two parallel experiments (one under UV and the other in dark) instead of running sequential experiment (i.e. running the experiment in the dark then turning on the UV lamp). These findings are supported by XPS analysis of the oxidation state of TiO2-sorbed As. Third, we demonstrate that photolysis by the light source itself, as well as the chemical composition of the solution (i.e. the effect of HEPES and the ionic strength), can significantly increase As(III) oxidation rates and need to be corrected. Finally, to determine the quantum yield of As(III) oxidation, we measured the photon absorption by the TiO2 photocatalyst. Our results showed that the quantum yield (Ø) for this oxidation reaction was low, and in the region of 0.1 to 0.2 %.